2022
DOI: 10.1093/nar/gkac683
|View full text |Cite
|
Sign up to set email alerts
|

ATRX histone binding and helicase activities have distinct roles in neuronal differentiation

Abstract: ATRX is a chromatin remodeler, which is mutated in ATRX syndrome, a neurodevelopmental disorder. ATRX mutations that alter histone binding or chromatin remodeling activities cluster in the PHD finger or the helicase domain respectively. Using engineered mouse embryonic stem cells that exclusively express ATRX protein with mutations in the PHD finger (PHDmut) or helicase domains (K1584R), we examine how specific ATRX mutations affect neurodifferentiation. ATRX PHDmut and K1584R proteins interact with the DAXX h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…We found that ATRX[R245C] mutant protein is sufficient to rescue the neuronal death phenotype present in mice lacking ATRX in the forebrain. This is supported by a recent study using CRISPR-edited mouse ESC-derived neural progenitor cells (NPCs) where a cell death phenotype was observed in cells lacking ATRX, but not in those expressing a stable mutant ATRX with two amino acid changes in the ADD domain that specifically abolish heterochromatin binding (Bieluszewska et al, 2022). This raises the question of whether mutating the ADD domain can cause elevated replicative stress, as has been described in Atrx-null NPCs (Watson et al, 2013) and myoblasts (Huh et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…We found that ATRX[R245C] mutant protein is sufficient to rescue the neuronal death phenotype present in mice lacking ATRX in the forebrain. This is supported by a recent study using CRISPR-edited mouse ESC-derived neural progenitor cells (NPCs) where a cell death phenotype was observed in cells lacking ATRX, but not in those expressing a stable mutant ATRX with two amino acid changes in the ADD domain that specifically abolish heterochromatin binding (Bieluszewska et al, 2022). This raises the question of whether mutating the ADD domain can cause elevated replicative stress, as has been described in Atrx-null NPCs (Watson et al, 2013) and myoblasts (Huh et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Numerous SNF2 proteins utilize the energy released by ATP hydrolysis to translocate along DNA, therefore remodeling DNA structures or DNA-protein interactions, as well as ATRX. ATRX’s histone-binding and chromatin-remodeling capabilities play a unique role in neuronal differentiation [ 26 ]. Mutations in the ATRX protein’s PHD finger have diverse effects on the genome-wide location of polycomb repressive complex 2 (PRC2), whereas mutations in the helicase domain induce loss in some places and gains in others.…”
Section: Molecular Structures Of Atrxmentioning
confidence: 99%